Effects of aluminized charge structures on blast wave propagation and the parameters of partially confined explosions - Feng Wang; Wei Xiao; Lili Tan; Zongwei Liu; Heng Wang; Zecheng Wang (AIP Advances)
The composite charge structure may have the potential to enhance the overall damage capability of the weapon. In this regard, three-dimensional LS-DYNA simulation software (dynamics calculation software from LSTC) was used to simulate the explosion process of charges in a partially confined space. The effects of different aluminized charge structures on the propagation and parameters of blast waves in a cubic cabin structure with a pressure relief port were obtained. The results showed that the reflected waves generated local pressure convergence at the junction and corner areas of adjacent walls in the cabin structure. The numbers of significant reflections of the blast waves at the center and corners of the wall were 3 and 2, respectively. The overpressure of the reflected wave at the corner was more than 3.2 times that at the center of the sidewall. Moreover, the number of reflections, overpressure ratio, and charge structure were not directly related. The advantages of composite structure charges in enhancing the overpressure and wave velocity of incident waves and the overpressure and impulse of reflected waves were not significant. However, the internal and external composite charge structure had more advantages than did the upper and lower structures, and its impulse TNT equivalent reached more than 70% of that of a single-structure explosive. The results can provide theoretical support and technical guidance for the design of charge structures and cabin structures.